Fronteiras terrestres da Espanha: os enclaves e as disputas geopolíticas - Camilo Pereira Carneiro Filho; João Lucas Zanoni (Confins)
The international terrestrial limits of Spain are the result of international treaties and warlike disputes that have occurred throughout history. At the beginning of the 21st century in the confines of Spanish territory there are still areas that are subject to interstate disputes. It is a set of enclaves, the possession of which, in some cases, is claimed simultaneously by Madrid and neighboring countries. This article presents an analysis of the border treaties and the history of disputes between countries that conform the current boundaries of the territories of Andorra, Llívia, Olivença, Gibraltar, Ceuta and Melilla. It aims to assess the role of the State as protagonist, rather than supranational organisms, in the contemporary international system. This is a qualitative research, from the perspective of International Relations, Political Geography and History, based on a bibliographic review and enriched with a field work at the borders of Spain and maps elaborated by the authors.